Strength Analysis of Ultra-High-Performance U-H-P Steel Fibre Reinforced Mortar Part of Concrete Using Rice Husk Ash & Nano Silica Fume - Kashif Alam; Arshad khan; Waqas Ur Rahman; Nadir Rehman Khattak; Muhammad Naveed Ur Rahman; Muhammad Abdur Rehman Hamid (Journal of ICT, Design, Engineering and Technological Science, 2024)
The purpose of this study is to provide Pakistani citizens with Ultra-High-Performance Concrete utilizing locally available resources. In an experimental study, steel fibres are combined with silica fume and rice husk ash when superplasticizers are present. Several different tests were done using completely different volumes and different amounts of ingredients from local supplies and steel fibres to investigate ultra-high-performance concrete. Results show that ultra-high-performance concrete can be produced using locally accessible material. There are differences in the compressive and flexural strengths of the Ultra High-Performance concrete. Every outcome is pleasing. Scanning electron microscopy and X-ray diffraction tests were also used to assess the ultra-high-performance concrete's microstructural analysis. The transition zone between fine aggregates and the cement paste is enhanced by the use of silica, according to X-ray diffraction and scanning electron microscopy test results. Dense packing is one of the main factors influencing concrete strength, and it is achieved by using a low water to-cement ratio. This observation is gained from Scanning Electron Microscopy and X-ray diffraction tests. The steel fibers in ultra-high-performance concrete inhibited the propagation of cracks in the matrix.